Evaluation of the effect of local exogenous application of osteopontin on wound healing in rats - Al Zamely, Zahraa R.; Kadhim, Enas F. (Journal of Baghdad College of Dentistry, 2018)
Background: Wound healing is a complex dynamical interaction between various cell types, the extracellular matrix, cytokines, and growth factors. osteoponetin is a substance that acts as an anti-inflammatory.Aims of study: The study was designed to identify the role of local exogenous applications of osteopontin on wound healing (in cheek skin).Materials and methods: Thirty adult male albino rats weighting an average of (250-300gm) used in this study, incisional wounds were made in the skin of the cheek of rat and they were divided into the following groups:A-Control group: 15 rats treated with 1Âµ l of normal saline B-Experimental groups: 15 rats treated with topical application of 1Âµl osteopontin. The scarification of animals were done for the healing intervals (1, 5 and 10 days) Histological analysis and assessment of number of inflammatory cell, Thickness and contraction of incision were performed for both experimental and control groups for all healing periods.Results: Histological analysis revealed that osteopontin accelerate wound healing of cheek skin and there was highly significant difference among studied groups in periods 1,5,10 days. Regarding mean values of epithelial thickness, inflammatory cell count and contraction of wound area have reported a highest value different in 1, 5 and 10 days durations. Conclusion: It can be concluded that application of osteopontin shown efficacy in the healing of skin wounds induced in rats.